THE SYNTHESIS OF BIOLOGICALLY ACTIVE PYRAZOLO[3,4-b]PYRIDINE AND PYRIDO[2,3-d]PYRIMIDINE DERIVATIVES - Kaya, Tansu Sezer; Turhan, Kadir (CHEM SOC ETHIOPIA, 2025)
In this study, firstly, benzylidene derivatives were obtained by Knoevenagel condensation using various aryl aldehydes and malononitrile in the presence of ethanol and then these differently substituted benzylidene compounds were substituted with 5-amino-3-methyl-1-phenylpyrazole and 6-amino-1-amino-1phenylpyrazole, respectively, 3-dimethyluracil and ytterbium(III) trifluoromethane-sulfonate [Yb(OTf)(3)] or acetic acid catalyzed pyrazolo[3,4-b]pyridine and pyrido[2,3-d]pyrimidine derivatives were synthesized (5a-5i), and the structures of these compounds, which were purified by different methods, were elucidated by spectroscopic methods such as FTIR, H-1-NMR, C-13-NMR and GS-MS. In our study, compounds 3a, 5a and 5c were synthesized for the first time. In addition, Yb(OTf)(3), one of the metal catalysts considered environmentally friendly catalysts, was used in this research. The genotoxic and antigenotoxic properties of the synthesized compounds were investigated in vitro using Ames Salmonella/microsome mutagenicity assay in the concentration range of 0.2-1.0 mM/plate. The results revealed that none of the compounds were mutagenic on three different Salmonella typhimurium strains up to the highest tested concentration. Moreover, in our study, 5a, 5e, 5f and 5h showed significant antigenotoxic effects ranging from moderate to strong against mutagen-induced DNA damage at relatively higher doses.
Keywords: Prido[2,3-d]pyrimidine; Pyrazolo[3,4-b]pyridine; Heterocyclic compounds; Benzylidene derivatives; MUTAGENICITY; Chemistry